One of the methods of muzzling mouths in authoritarian political dealings in the Holy Quran - Mohamed Lafta El Saeed; DR.najaf_lakzaee; dr. Mukhtar Sheikh Hosseini (Journal of College of Education, 2025)
The Holy Quran is a multi-visionary book that carries a religious vision represented by worship, a social vision in solving the problems of societies, an economic vision that includes spending, Khums and zakat, and a political vision that includes in the management of Community Affairs, which is the focus of our research, in which politics is described in its praised and vilified sections, which is defined as the management of the country and and the use of the most heinous methods of torture and imprisonment, including expulsion, exile and isolation, so we have shown that the means of muzzling We concluded that all the models mentioned by the Holy Quran that represented the voice of truth are the prophets and messengers, and the tyrants and oppressors are the rulers who derived their rule by mankind and not by the heavenly system, and we knew that the reform process is upright only by sacrifice by the preachers for the sake of rationality .
Keywords: Style-sleeve-deal-policy-explanation